Case for diagnosis. Atypical genital lesion - Sardinha, José Carlos Gomes (An Bras Dermatol, 2018)
We present a case of a penile lesion with a clinical appearance similar to Mondor penile disease (thrombosis of the dorsal vein of the penis) or penile sclerosing lymphangitis. Laboratory evaluation, however, showed a solid lesion, with no vascular component to Doppler ultrasonography and no treponema to immunohistochemistry. Histological and serological tests were compatible with secondary syphilis. The authors reinforce the need for the inclusion of syphilis in the differential diagnosis of penile cord injuries.